The effects of controlled smoking on heart period variability. - Nabors-Oberg, R.E (IEEE Engineering in medicine and biology magazine)
This article presents a study that examined the cardiovascular effects of a single session of repetitive cigarette smoking to investigate the possible development of short-term tolerance.